The mgrB gene as a key target for acquired resistance to colistin in Klebsiella pneumoniae - Poirel, Laurent; Jayol, Aurelie; Bontron, Severine; Villegas, Maria-Virginia; Özdamar, Melda; Türkoğlu, Salih; Nordmann, Patrice (Oxford University Press, 2015)
Objectives: Alterations in the PhoPQ two-component regulatory system may be associated with colistin resistance in Klebsiella pneumoniae. MgrB is a small transmembrane protein produced upon activation of the PhoPQ signalling system, and acts as a negative regulator on this system. We investigated the role of the MgrB protein as a source of colistin resistance in a series of K. pneumoniae. Methods: Colistin-resistant K. pneumoniae isolates were recovered from hospitalized patients worldwide (France, Turkey, Colombia and South Africa). The mgrB gene was amplified and sequenced. A wild-type mgrB gene was cloned and the corresponding recombinant plasmid was used for complementation assays. Clonal diversity was evaluated by MLST and Diversilab analysis. Results: Of 47 colistin-resistant isolates, 12 were identified as having a mutated mgrB gene. Five clonally unrelated isolates had an mgrB gene truncated by an IS5-like IS, while one clone also harboured an insertional inactivation at the exact same position of the mgrB gene, but with ISKpn13. Another clone harboured an insertional inactivation due to ISKpn14 at another location of the mgrB gene. Two clonally related isolates harboured an IS (IS10R) in the promoter region of mgrB. Finally, three clonally unrelated isolates harboured substitutions leading to anticipated stop codon in the MgrB protein. Complementation assays with a wild-type MgrB protein restored full susceptibility to colistin for all colistin-resistant isolates identified with qualitative or quantitative MgrB modifications. Conclusion: The inactivation or down-regulation of the mgrB gene was shown to be a source of colistin resistance in K. pneumoniae. Interestingly, identical genetic events were identified among clonally unrelated isolates.
WOS: 000350210800010
PubMed ID: 25190723
Keywords: Gene Inactivation; PhoPQ Regulatory System; Polymyxin; Klebsiella Pneumoniae